The effectiveness of breastfeeding incentive policies to combat early weaning:: a study conducted with the mothers of children attended at the childcare unit of CPN - Valente, Maria de Fátima Farias (2015)
There is a growing advancement of breastfeeding promotion policies. Breast milk supplies all the nutritional requirements for growth and development of the baby remain within the normal range for the period, being recommended as unique and adequate food in the first six months of life, especially as a protective factor against infectious diseases. Early weaning, ie, the introduction of other foods before six months is confirmed risk for infant mortality. This study aims: to know the women seen in the pediatric service of the Center of Natural Childbirth Ligia Barros Costa (ANC); assess the knowledge of these on the importance of breastfeeding; identify the eating habits of children seen at the ANC childcare service and meet the sociodemographic profile of mothers assisted in this service. A descriptive study of ethnographic, based on the principles of qualitative research. Held from October 15 to December 15, 2014, the ANC, in Fortaleza-CE. The population consisted of 65 mothers of children with an appointment during the study period and the sample consisted of 23 mothers gilts with zero son to six months old, assisted in the ANC child care service. Data were collected through individual interviews and home visits, and used a semi-structured form and through a group discussion where questions were posted to the group and discussed in this. Most: it is considered mixed; had not completed primary education; live in a stable relationship; live in their own home; not planned and did not want the pregnancy; the child was not placed to nurse at birth; demonstrated difficulty breastfeeding in the first attempts and has reasonable knowledge about the importance ofbreastfeeding. The exclusive breastfeeding rate (AME) found in the first month was around sixty-five percent; the second twenty six; in the third and twenty-one in the room was four percent. Not found child over four months of life in AME. The causes of early weaning were: lack of support from family and health professionals need to work or study; difficulty for the child get the chest; pain due cracking or breast engorgement; persistent crying of the child; little milk and the weak milk; the child does not want the chest; lack of patience or persistence of the mother; mother’s lack of will; afraid to be with fallen chest and a mother of twins, the pediatrician sent to complement. This work converges to the finding thatmothers have a reasonable knowledge of the importance of breastfeeding, but most fail to use that knowledge in practice.